"Welcome to the Border": National Geographic's Border Wars and the Naturalization of Border Militarization. Issue 1 (March 2014) - Dorr, Noam; Elcioglu, Emine Fidan; Gaydos, Lindsey
<x xml:space="preserve">Abstract</x> This article argues that National Geographic's highly rated television series Border Wars (BW) bestows border enforcement with a "natural" quality and precludes any discussion of alternatives to border buildup. It does this in three main ways. First, even though there is no actual war, the show frames federal agents as soldiers and their enforcement practices as soldiering. As such, escalation of border enforcement is portrayed as a fatalistic necessity in confronting a guerrilla‐like enemy. Second, to the extent that the show depicts actual encounters with crossers, it goes to great lengths to simplify the context and moral implications of crossers' stories. Third, BW fixes the viewer's gaze on objects—particularly illicit ones—and evades a discussion of the social processes hidden behind them. In these ways, BW essentializes cross‐border flows and justifies border enforcement.